Motion to Motion into perception - Van Zanten, Leonard (JOURNAL OF ADVANCES IN PHYSICS, 2021)
One of the most rewarding things in the sciences is to learn how things are put together, and how they operate. Our senses are not the only ones to come by movements in its particulars, seeing nature no less is in-and-by movement. Accordingly we come to a revelation in movements to movement, a revelation to show nature for its reality. Additionally; by illustration, the coordinates of movement are furnished to wit, magnetic, electric, light's velocity, and radial velocity.